2015
DOI: 10.1074/jbc.m114.603431
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-14 Both Sheds Cell Surface Neuronal Glial Antigen 2 (NG2) Proteoglycan on Macrophages and Governs the Response to Peripheral Nerve Injury

Abstract: Background: In the nervous system, NG2, an integral membrane chondroitin sulfate proteoglycan, is expressed by macrophages and progenitor glia. Results: Both NG2 shedding and axonal growth depend on the pericellular remodeling executed by MT1-MMP/MMP-14. Conclusion: MT1-MMP inhibition restores sensory axon regeneration and attenuates hypersensitivity caused by peripheral nerve injury. Significance: Our findings identify MT1-MMP as a novel therapeutic target in PNS injury and pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 65 publications
0
63
0
Order By: Relevance
“…At day 28 post-CCI, TIMP-2 levels normalized, whereas the levels of both proteases remained elevated, relative to naïve nerve, and the TIMP-MMP ratio obviously shifted in favor of MMPs. These patterns of MT1-MMP, MMP-2 and TIMP-2 mRNA expression in CCI nerve are similar to their mRNA and protein expression in crushed nerve [34]. …”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…At day 28 post-CCI, TIMP-2 levels normalized, whereas the levels of both proteases remained elevated, relative to naïve nerve, and the TIMP-MMP ratio obviously shifted in favor of MMPs. These patterns of MT1-MMP, MMP-2 and TIMP-2 mRNA expression in CCI nerve are similar to their mRNA and protein expression in crushed nerve [34]. …”
Section: Resultsmentioning
confidence: 81%
“…TIMP-2 both assists MT1–MMP in MMP-2 activation and inhibits an excessive activity of both enzymes [26]. In naïve sciatic nerve, the MT1-MMP, MMP-2 and TIMP-2 transcripts are constitutively expressed [19, 34]. However, the ratio of the TIMP-2 expression level relative to those of the proteases is high, suggesting the repression of the MMP activity [34].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We find that phenylephrine-and GTP␥S-stimulated MMP14 activation release HB-EGF (but not EGF (data not shown)) and that this shedding leads to tyrosine phosphorylation of EGFR. MMP14 is known to release other proteins from the plasma membrane (42). Perhaps GPCRs and heterotrimeric G proteins release other such entities.…”
Section: Discussionmentioning
confidence: 99%
“…30 It is known that PC coverage is varied depending on the tumor phenotype, showing different responsiveness to chemotherapy. 31,32 It has been demonstrated that PCs are present as a defective line in ovarian and colonic adenocarcinoma, while in pancreatic ductal adenocarcinoma and glioblastoma, they form glomeruloid structures. In most tumor types, PCs are present as a continuous line along ECs.…”
mentioning
confidence: 99%